Policing gun violence: strategic reforms for controlling our most pressing crime problem - Braga, Anthony Allan (Studies in crime and public policy, 2023)
In many U.S. cities, gun violence is the most urgent crime problem. High rates of deadly violence make a city less livable, dragging down quality of life, economic development, and property values. Drawing on fifty years of research and practical experience, Policing Gun Violence argues that it is possible for the police to create greater public safety while respecting the rights of individuals and communities. Anthony A. Braga and Philip J. Cook identify the most beneficial evidence-based practices, offering a comprehensive guide for deploying the authority and considerable resources of the police to reduce gun violence.